Progress towards eliminating Hib in Australia: an evaluation of Haemophilus influenzae type b prevention in Australia, 1 July 1993 to 30 June 2000. - Horby, P; Gilmour, R; Wang, H; McIntyre, P (2003)
The status of Haemophilus influenzae (Hib) disease and its prevention by vaccination was reviewed for the period 1997 to 2000. This forms the background to a change in national vaccine policy, from the use of two Hib vaccines to the use of PRP-OMP only throughout Australia from May 2000. Notifications of Hib in the 7-year period between 1993 and 2000 declined by 87 per cent among children 0-4 years of age; adjustment for likely under-reporting increase this to a 95 per cent reduction. Among age groups not included in the immunisation program, there was also a substantial decline in notified cases. Overall, a minimum 430 cases and 13 deaths were prevented by Hib immunisation annually in Australia. Enhanced Hib surveillance recorded 532 cases over seven years, with 353 in unvaccinated persons, 74 fulfilling criteria for true vaccine failure and 75 partially immunised. Of unvaccinated cases, 60 and 182 were eligible for routine and catch-up immunisation respectively. Although the overall incidence for 0-4 years of age declined from 15 to 1.2 cases per 100,000 population, the proportion of cases under six months of age increased from 11 per cent to 23 per cent. Overall vaccine effectiveness, estimated using data from the last five years of the program, was 83 per cent (95% CI 71-91%), increasing to 90 per cent (95% CI 83-94%) when adjusted for under-reporting to the Australian Childhood Immunisation Register. Among Aboriginal and Torres Strait Islander people, the incidence of invasive Hib disease fell from 4.6 cases per 100,000 population to 0.7 cases per 100,000 population but the proportion of cases now occurring among Aboriginal or Torres Strait Islander people increased significantly, from 7 to 15 per cent. The Hib immunisation program in Australia has been highly successful. Nevertheless, experience in Australia and elsewhere indicates that continued careful monitoring of Hib disease, with high quality laboratory surveillance, remains important.